Prevalence and prognostic significance of main metabolic risk factors in primary biliary cholangitis: a retrospective cohort study of 789 patients - Zhao, Dan-Tong; Yan, Hui-Ping; Han, Ying; Zhang, Wei-Ming; Zhao, Yan; Liao, Hui-Yu (Frontiers in Endocrinology, 2023)
Background: Metabolic risk factors in primary biliary cholangitis (PBC) have not been well described in China. Additionally, it is unclear whether these factors have an impact on the prognosis of PBC patients. Therefore, this study aimed to investigate the prevalence of main metabolic risk factors in PBC, and to evaluate their prognostic values for liver-related outcomes. Methods: A cohort of 789 PBC patients was retrospectively studied between July 2008 and September 2019 by investigating the main metabolic risk factors and analyzing liver-related outcomes. Results: At presentation, 271 (34.3%) patients had concomitant hyperlipidemia, 126 (16.0%) had hypertension, 94 (11.9%) had type 2 diabetes mellitus (T2DM), and 17 (2.2%) had nonalcoholic fatty liver disease (NAFLD). Hyperlipidemia was found to be associated with the lower risk of liver-related death [P<0.0001, hazard ratio (HR): 0.397, 95% confidence interval (CI): 0.268–0.588] and adverse outcomes (P<0.0001, HR: 0.487, 95% CI:0.367–0.646), while hypertension was noted as a risk factor for liver-related death (P=0.001, HR: 1.788, 95% CI:1.268–2.521) and adverse outcomes (P=0.014, HR: 1.417, 95% CI:1.074–1.869). Moreover, age ≥ 55 years old (P=0.005) and cirrhosis (P<0.0001) had superimposition effects on hypertension as a risk factor for liver-related death, while only cirrhosis (P<0.0001) had an effect on hypertension as a risk factor for adverse outcomes. Additionally, anti-sp100 was associated with adverse outcomes (P=0.013) in PBC patients with hypertension in univariate Cox regression analysis. Conclusion: Hyperlipidemia, hypertension, and T2DM were found as main metabolic risk factors in PBC in China. Hyperlipidemia indicated a benign clinical outcome of PBC, while hypertension indicated a poor outcome of PBC. Older age and cirrhosis had superimposition effects on hypertension for liver-related poor outcomes. Anti-sp100 might be associated with adverse outcomes, especially in PBC patients with hypertension.